Best Answer

2(q^2 - 5)

or

2(q - the square root of 5)(q + the square root of 5)

Q: How do you factor 2q squared minus 10?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

q3-q2+2q-2 = (q-1)(q2+2) = (q-1)(q+2.5i)(q-2.5i)

simply add the like terms: 4p -3p +2q -2q = p

70-q-q-2q = 70-4q = 80-4q = 10q=-10/4 = -5/2 = -2.5

8(2q) = (8*2)q = 16*q = 16q.

I'm not sure about the answer but what is 4p - 2q = 18? I need to know what p is.

Related questions

q3 - q2 + 2q - 2 = (q2+ 2)(q - 1).*If you are prepared to enter the realm of complex numbers(where i = âˆš(-1) ), then(iâˆš2)2 = 2(i2) = -2, andq2 + 2 = q2 - (iâˆš2)2= (q - iâˆš2)(q + iâˆš2);and, in this case, the complete factorization isq3 - q2 + 2q - 2 = (q2 + 2)(q - 1)= (q - iâˆš2)(q + iâˆš2) (q - 1).

2(2q+7)(3q-2)

q3-q2+2q-2 = (q-1)(q2+2) = (q-1)(q+2.5i)(q-2.5i)

It is the same as: -2q-3 as an algebraic expression

18 1i 2q 1i 2q -1i,-18 1i -2q 1i -2q -1i,0 1i -2q 18,-a 1i -2q u,-k 1i -2q k,-u 1i -2q a,-18 1i -2q 0,-1i 1i -2q -a,-1s 1i -2q -k,-26 1i -2q -u,-2g 1i -2q -18,k 1i 2q k,u 1i 2q a,18 1i 2q 0,1i 1i 2q -a,1s 1i 2q -k,26 1i 2q -u,2g 1i 2q -18,2q -42 2q -1i,2q -42 -2q -42 -2q -18,0 -42 -2q -3o,-a -42 -2q -3e,-k -42 -2q -34,-u -42 -2q -2q,-18 -42 -2q -2g,-1i -42 -2q -26,-1s -42 -2q -1s,-26 -42 -2q -1i,-2g -42 -2q -18,0 -42 2q -3o,a -42 2q -3e,k -42 2q -34,u -42 2q -2q,18 -42 2q -2g,1i -42 2q -26,1s -42 2q -1s,26 -42 2q -1i,2g -42 2q -18,0 1i 0 i4 1s qs,0 i4 -1s qs,0 5k 34 h6,0 5k -2q h6,-1i 1i 2q 1i,2q u a 1i,2q 18 0 1i#-18 -34 -u -34 -k -2q -k -2g -u -26 -18 -26 -1i -2g -1i -2q -18 -34,u -34 18 -34 1i -2q 1i -2g 18 -26 u -26 k -2g k -2q u -34,-1i -a -u 0 18 0 1s -a,0 -1i -a -u 0 -u,-a 1i 0 1s#B 0 -3e 8e,B 0 u 2q,G -1s -34 9r,G -1s k 71,G 1s k 47,G 1s -34 1d,G 0 -42 b8,G -2q -18 8e,G 0 1i 5k,G 2q -18 2q

simply add the like terms: 4p -3p +2q -2q = p

(3b + 4x)(2q + v)

70-q-q-2q = 70-4q = 80-4q = 10q=-10/4 = -5/2 = -2.5

2q ÷ q = 2

The question is incomplete in the sense that there is no +/- sign between q2 and 2q. Considering plus '+' sign. q3 - q2 + 2q - 2 q2(q - 1) + 2(q - 1) (q2 + 2)(q - 1) Considering minus '-' sign. q3 - q2 - 2q - 2 The expression can't be factored. However if we consider the question complete then it is written as: q3 - q2(2q) - 2 q3 - 2q3 - 2 -q3 - 2 -(q + 21/3)(q2 - 21/3 + 22/3)

( 2q - 10 )

Let f(X)=2X2+6X+3 So f(-p)=f(2q) or 2p2-6p+3=8q2+12q+3 or p2-3p=4q2+6q or p2-4q2=3p+6q or (p+2q)(p-2q)=3(p+2q) so p-2q=3